Recontextualizing the Medina Charter: Consensus-Based Political Communication for Contemporary Plural Societies - Hasrat Efendi Samosir; Md Noor Bin Hussin; Sudianto; Marlina; Azman (Faculty of Sharia, IAIN Metro, 2025)
This study explores the Constitution of Medina as an early model of prophetic political communication grounded in consensus, offering a relevant framework for managing diversity and fostering social cohesion in pluralistic societies. Utilizing a qualitative library research method, the study draws upon the primary source—the text of the Constitution of Medina—and integrates secondary literature from the field of political communication. The data were analyzed through content analysis to identify underlying communicative principles and political strategies within the Charter. The findings reveal that the Constitution operationalizes participatory dialogue and peaceful conflict resolution mechanisms, aligning closely with contemporary consensus-based political communication theories. These principles served not only to manage inter-group tensions but also to build a cooperative and just social order. The study concludes that the Constitution of Medina is not merely a historical document but a normative model that offers practical insights into inclusive governance, interfaith cooperation, and the ethical foundations of political discourse. Its relevance is especially significant today, where polarized societies seek coexistence and constructive engagement frameworks. Thus, the Medina Charter is relevant as a prophetic guide for inclusive political communication in multicultural and multireligious contexts. This study contributes to Islamic political thought and communication by providing a normative and historically grounded model for inclusive governance. It bridges classical Islamic sources with contemporary political communication theory, offering a framework applicable to modern pluralistic societies seeking ethical and participatory governance models.